T-cell-derived interleukin-17 regulates the level and stability of cyclooxygenase-2 (COX-2) mRNA through restricted activation of the p38 mitogen-activated protein kinase cascade - Faour, Wissam (2003)
Although interleukin-17 (IL-17) is the pre-eminent T-cell-derived pro-inflammatory cytokine, its cellular mechanism of action remains poorly understood. We explored novel signaling pathways mediating IL-17 induction of the cyclooxygenase-2 (COX-2) gene in human chondrocytes, synovial fibroblasts, and macrophages. In preliminary work, recombinant human (rh) IL-17 stimulated a rapid (5–15 min), substantial (>8-fold), and sustained (>24 h) increase in COX-2 mRNA, protein, and prostaglandin E2 release. Screening experiments with cell-permeable kinase inhibitors (e.g. SB202190 and p38 inhibitor), Western analysis using specific anti-phospho-antibodies to a variety of mitogen-activated protein kinase cascade intermediates, co-transfection studies using chimeric cytomegalovirus-driven constructs of GAL4 DNA-binding domains fused to the transactivation domains of transcription factors together with Gal-4 binding element-luciferase reporters, ectopic overexpression of activated protein kinase expression plasmids (e.g. MKK3/6), or transfection experiments with wild-type and mutant COX-2 promoter constructs revealed that rhIL-17 induction of the COX-2 gene was mediated exclusively by the stress-activated protein kinase 2/p38 cascade. A rhIL-17-dependent transcriptional pulse (1.76 ± 0.11-fold induction) was initiated by ATF-2/CREB-1 transactivation through the ATF/CRE enhancer site in the proximal promoter. However, steady-state levels of rhIL-17-induced COX-2 mRNA declined rapidly (<2 h) to control levels under wash-out conditions. Adding rhIL-17 to transcriptionally arrested cells stabilized COX-2 mRNA for up to 6 h, a process compromised by SB202190. Deletion analysis using transfected chimeric luciferase-COX-2 mRNA 3′-untranslated region reporter constructs revealed that rhIL-17 increased reporter gene mRNA stability and protein synthesis via distal regions (–545 to –1414 bases) of the 3′-untranslated region. This response was mediated entirely by the stress-activated protein kinase 2/p38 cascade. As such, IL-17 can exert direct transcriptional and post-transcriptional control over target proinflammatory cytokines and oncogenes.